Complete Midwifery Care In Very High-Risk Pregnancy - Dintya Ivantarina; Dwi Yuliawati; Fitri Yuniarti; Wulan Anggraini (Institute of Computer Science (IOCS), 2021)
A very high-risk pregnancy is a risk group for pregnant women with the highest number of maternal and neonatal deaths. One way that can be carried out to prevent maternal and infant complications is to provide complete midwifery care. The purpose of this case study is to provide complete midwifery care to Mrs.